Leveraging Smart City Technologies Solutions for Climate Change in Ghana: Implications for Urban Planning and Policy - , Christian Kofi Sarpong, Prince Attakora (Archives of Current Research International, 2025)
Ghana’s urban centres are increasingly vulnerable to the effects of climate change, including rising temperatures and erratic rainfall patterns, as well as recurrent flooding. Addressing these issues requires innovative, technology-based solutions. This paper examines the role of smart city technologies in mitigating and adapting to climate change within the Ghanaian space economy through a systematic review of papers published from 2009-2025. The paper identifies nine priority domains: carbon emissions reduction, resource optimization, environmental monitoring, urban mobility, community engagement, renewable energy integration, sustainable infrastructure, climate resilience, and policy support, where smart technologies can make significant contributions. The finding revealed that through the integration of intelligent systems in transportation, energy, and urban planning, smart cities are capable of reducing climate impacts and enhancing citizens' quality of life. By contextualizing global experiences within Ghana’s unique socio-political and infrastructural setting, this paper contributes novel, localized insights into the potential and challenges of these technologies for inclusive, sustainable urban transformation. The paper proposes coordinated policy frameworks, targeted investment, and inclusive governance to leverage digital innovations for climate action in Ghanaian cities.